RISK ASSESSMENT OF NEW FERRY SHIP CONSTRUCTION IN INDONESIA USING THE FAILURE MODE EFFECT AND ANALYSIS (FMEA) METHOD - Ariany, Zulfaidah; Pitana, Trika; Vanany, Iwan (Journal of Applied Engineering Science, 2023)
This study aims to identify, calculate the impact rating, and mitigate the effects on new ferry construction in Indonesian shipyards. The Risk Matrix method and Failure Mode and Effect Analysis (FMEA) are employed to analyze risk levels. Data were collected through field observations and interviews regarding risks and potential delays in ship components. The results reveal 23 potential hazard sources, with two risks having the highest Risk Priority Number (RPN) values. Assessment based on the quality control section that causes delays in the arrival of ME/AE/pumps and other mechanical equipment 366.18. Assessment of the Project Leader process Delay in the assembly/fabrication/erect process 519.49. Part of production leadership Delay in assembly/fabrication/erecting processes 317.37. Based on the assessment of the three sections, high-risk potential occurs in ship hull work, Delays in assembly/fabrication/erect processes, and machining work Delays in the Arrival of ME/AE/Pumps and Machine Equipment. The risk matrix indicates high-risk ratings for component delays in ship hull work, medium risk for machining work, and the low risk for electrical work and other components. The next step is to assess the potential of domestic components and design a component availability model for new shipbuilding, including imported components. This research offers valuable insights for RoRo ferry shipping stakeholders, helping them understand the mechanisms causing delays in new ship construction and guiding efforts to reduce the risk of failure.
Keywords: failure mode and effect analysis, risk matrix, ferry, RPN, new ship